WTAP dysregulation‐mediated HMGN3‐m6A modification inhibited trophoblast invasion in early‐onset preeclampsia. Issue 12 (22nd November 2022) - Bian, Yue; Li, Jiapo; Shen, Hongfei; Li, Yuanyuan; Hou, Yue; Huang, Ling; Song, Guiyu; Qiao, Chong
Abstract: Early‐onset preeclampsia (ePE) originates from abnormal implantation and placentation that involves trophoblast invasion, but its pathophysiology is not entirely understood. N6‐methyladenosine (m6A) regulators mediate the progression of various cancers. The invasiveness of trophoblast cells is similar to that of tumor cells. However, little is known regarding the potential role of m6A modification in ePE and the underlying mechanism. This study aimed to explore the m6A level in placental tissue samples collected from ePE patients and to investigate whether m6A modification was an essential part of PE pathogenesis. The m6A level in placental tissue samples of 80 PE participants was examined. MeRIP‐microarray, RNA‐Seq, luciferase reporter assay, and RNA immunoprecipitation chip (RIP) assay were performed. The m6A level in the ePE group was significantly reduced compared with the control group. Wilms' tumor 1‐associating protein (WTAP) regulated trophoblast cell migration and invasion. Mechanistically, the high mobility group nucleosomal binding domain 3 (HMGN3) gene was a target gene of WTAP in trophoblast ( p  < .05). WTAP enhanced the stability of HMGN3 mRNA through binding with its 3'‐UTR m6A site(+485A, +522A). HMGN3 was recognized by m6A recognition protein insulin‐like growth factor 2 mRNA‐binding protein 1 (IGF2BP1), which was inhibited when knocking down WTAP. Both m6A and WTAP levels were downregulated in ePE. The m6A modification mediated by WTAP/IGF2BP1/HMGN3 axis might contribute to abnormal trophoblast invasion. Our work provided a foundation for further exploration of RNA epigenetic regulatory patterns in ePE, and indicated a new treatment strategy for ePE.